A Review on Correlating Gas District Cooling (GDC) Model with Data Center (DC) Operation for Environmental and Economic Performance - Omar, N.S.S.B. (Springer, 2020)
This study is a review in finding correlation between supply of chilled water and energy from Gas District Cooling (GDC) model with cooling and energy demand from Data Center (DC) operations. The architecture is called GDC-DC. This architecture was introduced by Hitachi Research in Universiti Teknologi PETRONAS (UTP) as UTPâs GDC houses the campus region (academic buildings, chancellor complex and mosque) with electrical energy and chilled water for air conditioners. Based on review from previous research on GDC-DC operations in UTP, the current GDC-DC operations is not meeting the real-time job requirements and energy requirements by DC. Apart from that, DC configurations areÂ inappropriate and non-optimized thus, increasing the power usage of DC and cooling demand. This will contribute to high operational cost on DC and carbon footprint issue due to rise of higher power generation. Eventually affecting the environment and economic performance of GDC-DC. Therefore, this paper aims to find the best real-time scheduling algorithm in DC that will contribute to an optimized DC which will affect the cooling demand. A review is done to help finding the relevant real-time job schedulers which will further to be deployed in the DC model from UTP. Â© 2020, Springer Nature Singapore Pte Ltd.